KAJIAN KONSENTRASI JUS SEMANGGI DAN LAMA PERENDAMAN TERHADAP PENURUNAN LOGAM BERAT KUPANG MERAH - Enny Karti Basuki; Sri Winarti (Agroindustrial Technology, University of Trunojoyo Madura, 2019)
Red kupang lives permanently dan eats by filtering food in waters so that it has high potential to be contaminated with heavy metals. The presence of heavy metals in kupang can cause health problems if consumed by humans. One of the efforts to reduce the heavy metal of kupang merah by adsorption method uses natural ingredients such as clover which is rich in secondary metabolites. The content of secondary metabolites in plants acts as a binder for heavy metals. The purpose of this study was to determine the concentration of clover juice dan the best time of immersion in kupang merah to reduce the level of heavy metals in kupang merah meat. This study used a complete random factorial pattern design with two factors with 2 replications. First factor: clover juice concentration 10%, 20%, 30% dan second factor: contact time is 60 minutes, 90 minutes, 120 minutes. The results of clover analysis showed that fresh clover contained terpenoids/steroids, saponins, flavonoids, polyphenols dan phenols in total 86.935 ± 2.004 mg TAE/gram. The results of fresh red kupang analysis showed protein content of 9.82 ± 0.3111%, water content of 81.527±0.545%, ash content of 1.840±0.014%, copper metal content of 47.491±0.386 ppm, lead 21.309±1.93 ppm, chromium 2,333±1,102 ppm, cadmium 1,648±0,083 ppm dan mercury 0,539±0,027 ppm. The best treatment in the study of the best metal content reduction at 30% clover juice concentration and 120 minutes soaking time can reduce the contamination of kupang Merah heavy metals, namely Cu to 19.862 ppm (down 58.177%), Pb to 0.886 ppm (down 95.842%), Cr to 0.758 (down 67.609%), Cd becomes 0.813 ppm (50.668%), Hg becomes 0.024 ppm (95.547%). The characteristics of kupang Merah meat after soaking are 9.10% protein content, 1.781% ash content dan 84.506% moisture content.